2012
DOI: 10.1128/mcb.06206-11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chromatin Dynamics during Glucocorticoid Receptor Activation

Abstract: dSteroid hormone receptors initiate a genetic program tightly regulated by the chromatin environment of the responsive regions. Using the glucocorticoid receptor (GR) as a model factor for transcriptional initiation, we classified chromatin structure through formaldehyde-assisted isolation of regulatory elements (FAIRE). We looked at dynamic changes in FAIRE signals during GR activation specifically at regions of receptor interaction. We found a distribution of GR-responsive regions with diverse responses to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…Similar results were obtained using formaldehyde-assisted isolation of regulatory elements and deep sequencing (FAIRE seq; see Supplementary information S1 (table)). In this case, pre-existing FAIRE seq signal indicative of open chromatin increased on glucocorticoid stimulation, suggesting that GR interacts with pre-existing open chromatin and then further alters the chromatin environment 39 . By contrast, negative regulatory DNA sequence (NRS) motifs were identified proximal to a subset of GBSs as anti-correlates to GR genomic occupancy.…”
Section: Gr-genome Interactionsmentioning
confidence: 85%
“…Similar results were obtained using formaldehyde-assisted isolation of regulatory elements and deep sequencing (FAIRE seq; see Supplementary information S1 (table)). In this case, pre-existing FAIRE seq signal indicative of open chromatin increased on glucocorticoid stimulation, suggesting that GR interacts with pre-existing open chromatin and then further alters the chromatin environment 39 . By contrast, negative regulatory DNA sequence (NRS) motifs were identified proximal to a subset of GBSs as anti-correlates to GR genomic occupancy.…”
Section: Gr-genome Interactionsmentioning
confidence: 85%
“…The most specific long-range interactions between promoters and enhancers were found within the boundaries of TADs (Burd et al 2012), and the loci within a TAD are proposed to be sufficiently dynamic to allow reproducible contacts between a gene and its regulatory elements Dekker 2012, 2013). Consistent with this idea, we found that the 100-kb regions around GR-responsive genes are preferentially associated with hormone-responsive, dynamic DHSs.…”
Section: Discussionmentioning
confidence: 99%
“…ChIP assays were performed as previously described using ERα antibody (Santa Cruz Biotechnology, Santa Cruz, CA) [15]. Sequencing libraries were prepared from ChIP enriched DNA using the Tru-seq Chip Sample Prep Kit (Illumina, San Diego, CA) according to manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%